Implementasi Model Pembelajaran Kooperatif Tipe Quiz- Quiz Trade Dalam Meningkatkan Hasil Belajar Pada Mata Pelajaran Pendidikan Agama Islam - Hudamahya, Aulia; Saputra, Edi (Prodi Pendidikan Keagamaan Islam, 2024)
This study aims to determine the use of the Quiz-Quiz Trade cooperative learning model in improving student learning outcomes in PAI subjects at SDN 39 Ambacang. Using a qualitative method with a descriptive approach, data were collected through observation, documentation, and interviews. The results indicate that: (1) The planning of the Quiz-Quiz Trade model is guided by the curriculum and is reflected in the lesson plans. (2) During implementation, teachers prepare and deliver learning materials, provide stimuli and responses, assign Quiz-Quiz Trade tasks, ensure task accountability, and conduct evaluations. (3) Student learning outcomes using this model are divided into intrinsic outcomes (challenge, curiosity, self-control, and fantasy) and extrinsic outcomes (parental sanctions, rewards, punishments, and praise). (4) Evaluation reveals that PAI teachers do not use the observation sheets for student discussions as listed in the lesson plans and rely on multiple-choice tests that do not meet HOTS criteria, limiting the effectiveness in improving student learning outcomes in class V SDN 39 Ambacang.